The Frequency of Major and Minor Amputations in Patients with Diabetic Foot - Gul Muhammad, Iftikhar Ahmed, Adeel Ur Rehman Kandan, Muhammad Faisal Bacha, Wajeed Gul Bangash, Muhammad Noaman6, Shahid Mahmood (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Diabetic foot (DF) is the main cause of non-traumatic lower extremity amputations. Major and minor amputations in diabetic foot disease are benchmark indicators of natural history and prognosis of disease. This study will help to prevent DF complications and improve care of diabetes foot. Objectives: To determine the frequency of major and minor amputations and the factors responsible for patients with diabetic foot coming in surgical OPD. Methods: All the patients who presented in hospital with diabetic foot ulcer were included in this study from 01-11-2019 to 30-10-2020. One hundred and forty patients of either gender with age between 20 to 80 years with diabetic foot ulcers of any grade were enrolled in the study. Frequency of minor and major amputations was measured. Results: Out of three hundred and twenty patients, 16.4% (n=69/320) patients underwent lower limb amputations. Minor amputations were made in 12.1% (n=51/320) and major were made in 4.3% (n=18) of patients. Frequency of amputations was significantly higher in older age groups (61-80 years), patients with longer disease duration (>10 years), with poor glycemic control (HBA1-C>8.0) and patients with higher grades of ulcers (grades III and IV) (P<0.05). No significant difference was observed among gender, different education and occupation groups (P>0.05). Conclusions: A significant percentage of patients with diabetic foot ulcers underwent lower limb amputations, which was significantly associated with older age, longer disease duration, poor glycemic control and higher grades of ulcers. Keywords: Diabetic foot, Lower limb amputation, diabetic ulcers.